Characterization of tunnel mutants reveals a catalytic step in ammonia delivery by an aminoacyl‐tRNA amidotransferase. Issue 18 (23rd August 2016) - Zhao, Liangjun; Rathnayake, Udumbara M.; Dewage, Sajeewa W.; Wood, Whitney N.; Veltri, Anthony J.; Cisneros, G. Andrés; Hendrickson, Tamara L.
Abstract : The Helicobacter pylori Asp‐tRNA A sn /Glu‐tRNA G ln amidotransferase (GatCAB) utilizes an uncommonly hydrophilic, ~ 40 Å ammonia tunnel for ammonia/ammonium transport between isolated active sites. Hydrophilicity of this tunnel requires a distinct ammonia transport mechanism, which hypothetically occurs through a series of deprotonation and protonation steps. To explore the initiation of this relay mechanism, the highly conserved tunnel residue D185 (in the GatA subunit) was enzymatically and computationally investigated by comparing D185A, D185N, and D185E mutant enzymes to wild‐type GatCAB. Our results indicate that D185 acts as an acid/base residue, participating directly in catalysis. To our knowledge, this is the first example of acid/base chemistry in a glutamine‐dependent amidotransferase ammonia tunnel. Abstract : GatCAB uses an unusually hydrophilic ammonia tunnel to transfer ammonia between active sites. A novel proton relay mechanism may facilitate ammonia transport through this tunnel. Residue D185, near the entrance of this tunnel, is proposed to act as a catalytic residue. Enzyme assays and computational correlation analyses support a role for D185 in ammonia delivery. These results are the first demonstration of acid/base chemistry within an ammonia tunnel.